Creating Bridges: The Vision of the UCLA-Oxford Empirical Research in Entrepreneurship Conference - Flamholtz, Eric G. (Senate Hall, 2005)
During the past few decades, we have witnessed the beginnings of rise of many spectacularly successful entrepreneurial firms and perhaps even more spectacularly successful entrepreneurial failures. We have watched in awe the rise of Microsoft, Dell, Amgen, E-Bay, Amazon.com, Starbucks, and Virgin. We have seen the meteoric rise and flameout of People Express, Osborne Computer, and Global Crossing. This leads too many unanswered questions: Who are the entrepreneurs? Are they different from people who inhabit large, established organizations like Nestle and Nippon Steel, Reuters and Roche, Toyota and Total, GE and General Motors? Is there an "entrepreneurial personality"? Are entrepreneurs different in Shanghai than in San Francisco; in Los Angeles and in Lucerne? How do they get the funds to create new ventures? Are established "ties" and connections more important than ideas and business plans? Why are some entrepreneurial companies successful over the long term while others experience difficulties or even failure after promising starts? Is it necessary for entrepreneurships to make a transformation or metamorphosis to something else over time? If so, it is simply a function of size and complexity? How do organizations make the transition from entrepreneurship to professionally management without losing the entrepreneurial spirit? How do large established companies, which no longer have their founder in place, continue the spirit of entrepreneurship? We have also seen the development of entrepreneurship as a field of study in business schools and the emergence of entrepreneurship as an area for research. Those of us who embraced entrepreneurship as an area of research understand the promise of the field and recognize that it has not yet reached the critical mass of other scholarly disciplines.
Keywords: entrepreneurship research agenda